2016
DOI: 10.3390/nu8030049
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Mouth Rinse Maintains Muscle Electromyographic Activity and Increases Time to Exhaustion during Moderate but not High-Intensity Cycling Exercise

Abstract: The aim was to investigate the influence of a carbohydrate (CHO) mouth rinse on the vastus lateralis (VL) and rectus femoris (RF) electromyographic activity (EMG) and time to exhaustion (TE) during moderate (MIE) and high-intensity cycling exercise (HIE). Thirteen participants cycled at 80% of their respiratory compensation point and at 110% of their peak power output to the point of exhaustion. Before the trials and every 15 min during MIE, participants rinsed with the CHO or Placebo (PLA) solutions. The root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 26 publications
3
33
1
4
Order By: Relevance
“…Nevertheless, even without significant difference, time to exhaustion was 4.4% longer in CHO than in PLA, and was associated with a lower RPE, possibly because CHO mouth rinse may have activated brain regions (including areas of the insula/frontal operculum, orbitofrontal cortex and striatum) involved in reward 8,9 . This result corroborates recent findings 28 showing that even with a reduced RPE at the exhaustion after CHO mouth rinse, exercise endurance at 110% of PPO was not altered after a CHO mouth rinse. It was showed that CHO rinsing is able to maintain neuromuscular activation (i.e., the electromyographic signal of the vastus lateralis) along of time during moderate-, but not high-intensity exercise 28 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, even without significant difference, time to exhaustion was 4.4% longer in CHO than in PLA, and was associated with a lower RPE, possibly because CHO mouth rinse may have activated brain regions (including areas of the insula/frontal operculum, orbitofrontal cortex and striatum) involved in reward 8,9 . This result corroborates recent findings 28 showing that even with a reduced RPE at the exhaustion after CHO mouth rinse, exercise endurance at 110% of PPO was not altered after a CHO mouth rinse. It was showed that CHO rinsing is able to maintain neuromuscular activation (i.e., the electromyographic signal of the vastus lateralis) along of time during moderate-, but not high-intensity exercise 28 .…”
Section: Discussionsupporting
confidence: 92%
“…This result corroborates recent findings 28 showing that even with a reduced RPE at the exhaustion after CHO mouth rinse, exercise endurance at 110% of PPO was not altered after a CHO mouth rinse. It was showed that CHO rinsing is able to maintain neuromuscular activation (i.e., the electromyographic signal of the vastus lateralis) along of time during moderate-, but not high-intensity exercise 28 . Probably, an activation of reward areas with CHO rinse is able to reduce feelings of fatigue during the high-intensity exercise, but it is not sufficient to translate in an improvement in the exercise performance in this kind of exercise.…”
Section: Discussionsupporting
confidence: 92%
“…The presence of carbohydrate in the mouth stimulates a group of sensory receptors that activates some areas of the brain that are associated with reward and motor control, 25 ultimately reducing RPE. 27 Interestingly, this central effect of carbohydrate supplementation during exercise seems to be more pronounced when endogenous carbohydrate availability is low. 28 Therefore, it seems reasonable to assume that any central effect of carbohydrate ingestion during exercise would become more important as the exercise progresses and endogenous carbohydrate availability decreases.…”
Section: Discussionmentioning
confidence: 99%
“…2) Utilizamos um TIM para testar as intervenções propostas, pois ambas as manipulações realizadas no presente estudo (i.e. FM e bochecho com CHO) respondem diferentemente de acordo com a intensidade do exercício (BASTOS-SILVA et al, 2016;DUNCAN et al, 2015).…”
Section: Limitações E Aspectos Metodológicosunclassified
“…Tem sido proposto que o modelo de FM esteja ligado a alterações ocorridas no sistema nervoso central, principalmente em regiões corticais como córtex pré-frontal (CPF), córtex orbitofrontal e córtex cingulado anterior, as quais seriam possivelmente mediadas pela ação de , um efeito possivelmente associado à ativação dessas regiões cerebrais.Além disso, é possível que o bochecho com CHO tenha diferentes efeitos quando utilizado em exercício de diferentes intensidades(BASTOS-SILVA et al, 2016). Por exemplo,Bastos investigaram o efeito do bochecho com CHO sobre testes até a exaustão em diferentes intensidades.…”
unclassified